Complex oscillations and two-parameter bifurcations of a memristive circuit with diode bridge rectifier. (November 2019) - Sadecki, Jan; Marszalek, Wieslaw
Abstract: One- and two-parameter bifurcation diagrams of an oscillating circuit (based on a low-pass Sallen-Key topology) with a full-wave memristive rectifier are presented. The diagrams detail peculiar bursting responses of the circuit together with various interactions of chaotic attractors of the circuit when certain parameters vary. The full-wave rectifier has three fingerprints of memristors with a pinched hysteretic current-voltage characteristic. Illustrative examples with both one- and two-parameter bifurcation diagrams are included. A brief description of the parallel computations used to obtain the two-parameter color diagrams is also provided.